The world needs BRICS countries to build capacity in invasion science - Measey, John (PLoS Biol, 2019)
Developed countries are producing policies to reduce the flow of invasive species and control or eradicate existing invasions, but most developing countries are under-resourced to tackle either aspect without help. Emerging economies, such as Brazil, Russia, India, China, and South Africa (BRICS), are responsible for donating many of the world’s invasive species that have the potential to reach nearly all terrestrial biomes. Implementing a proactive ‘facilitated network’ model is urgently required to build capacity and stimulate effective appropriate invasion science. We contend that creating a BRICS network of invasion scientists will have the immediate impact required to meet future policy demands.